A qualitative study of nurses' perspectives of caring for children with intellectual disability and their families in a paediatric acute care setting. (December 2019) - Lewis, Peter; Wilson, Nathan J; Jaques, Hayden; O'Reilly, Kate; Wiese, Michele
Children with intellectual disability (ID) experience chronic and pervasive limitations across intellectual and adaptive functioning. They are also at risk of developing co-morbidities. They are likely to be hospitalised more frequently and for longer periods of time than other children. The purpose of this study was to understand the experiences of nurses when caring for children and teenagers with ID in an acute paediatric hospital setting. The aim of the research was to inform future directions for the delivery of equitable and effective care for this vulnerable population. This study used a qualitative thematic analysis of individual interviews conducted with eight registered and enrolled nurses who provided care to children and adolescents with ID in an Australian paediatric acute hospital setting. Themes which emerged from this analysis were (1) Recognising similarities and managing differences; (2) Nurse–parent relationships; and (3) Caring for children with ID requires additional time. This study highlights that navigating care delivery and relationships when working with young people with ID and their caregivers in an acute care setting is complex. Nursing children with ID in hospital requires sophisticated skills. To ensure quality healthcare for patients with ID, a range of strategies are proposed.